Standard specifications for highway bridges (American Association of State Highway and Transportation Officials, 2002)
"The Standard Specifications for Highway Bridges are intended to serve as a standard or guide for the preparation of State specifications and for reference by bridge engineers. Primarily, the specifications set forth minimum requirements which are consistent with current practice, and certain modifications may be necessary to suit local conditions. They apply to ordinary highway bridges and supplemental specifications may be required for unusual types and for bridges with spans longer than 500 feet"--Page v
Cover title.
Keywords: Bridges -- Specifications -- Handbooks, manuals, etc.; Bridges -- Design and construction.; elektronické knihy; electronic books